PERENCANAAN EMBUNG GUWOREJO KECAMATAN TAROKAN KABUPATEN KEDIRI - Yuono Mugi Kuncoro; Djoko Trijanto; Medi Efendi (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
In dry season Tarokan Sub-district of Kediri, often suffers from drought, so a small dam (embung) was required. The objectives of the study are to determine the dimension of the dam, its spillway and to analyze its stability. The required data were of rainfall, topographic maps, soil, and population.The initial design was hydrologic analysis by finding out the planned discharge Q50 and determining the water volume of inflow. To determine the effective catchment ponds, capacity analysis using topographical data and comparing the volume of water available. And analysis of spillway to determine the flood water level.The analyses result, the amount of the water needs of a population of 258.854.400m3, and the magnitude of the draft Q50 discharge of in 4.027 m3/sec (The room for sediment is 29,234.9 m3 at elevation 1 m from the bottom of the pool); 390,000m3 effective capacity at +131.75 elevation, and flood water level at +132.75 elevation. The dimension of embung main dam is 6 m deep; embung crest at +133.00 elevation ; 3m wide embung crest ; 1:3 upstream slope; 1 : 2.25 downstream slope ; 10 m wide spillway channel 1 : 1 slope of wall of spillway channel ; and crest of spillway at +131.75. Geostudio software was used to calculate the figures safety against sliding. Keywords: embung, spillway, embung dimensions, slope stabilty